Integrating animation and video materials into virtual reality interface-a case study of Islamic architectural heritage complex - Jahn Kassim, Puteri Shireen (s.n, 2012)
This paper present the development of an e-learning application combining virtual reality (VR) and multimedia techniques which features interactive real time walkthroughs of highly accurate 3D architectural and ancient city models for the development of an innovative tool in teaching of history and prototypical development combines multimedia, architectural and information technology specialists.